Synthesis of Dibenzalacetone using Sonochemistry and Its Antibacterial Activity Against Escherichia coli - Yuliana Purwaningsih; Erwin Indriyanti; Mighfar Syukur; Dyan Wigati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
The synthesis of dibenzalacetone, a ketone compound with potential antibacterial properties, especially against Escherichia coli, has typically involved time-consuming methods. This study adopts sonochemistry, an increasingly popular technique recognized for its efficiency and quick yield. The aim is to synthesize dibenzalacetone using the sonochemical method and evaluate its antibacterial efficacy against E. coli. The synthesis process includes a cross-aldol condensation reaction between acetone and benzaldehyde, catalyzed by NaOH, conducted in an ultrasonic bath at 35 °C for 1-5 minutes. The optimal synthesis condition, achieved in 4 minutes, resulted in a 76.56% yield of dibenzalacetone, characterized as a bright yellow solid with a melting point of 111-114°C. Techniques such as FT-IR, GC-MS, 1H-NMR, and 13C-NMR spectrometry were employed for structural characterization. The FTIR analysis revealed various functional groups, including C=O ketone, C=C aromatic, and C-H aromatic. GC-MS data confirmed the molecular weight of dibenzalacetone at m/z 234.1. Furthermore, 1H-NMR and 13C-NMR analyses provided detailed insights into the compound's chemical shifts and structural groups, affirming the successful synthesis of dibenzalacetone. The antibacterial activity of dibenzalacetone against E. coli was tested at concentrations ranging from 5% to 20%. Notably, at a 15% concentration, dibenzalacetone exhibited antibacterial activity comparable to amoxicillin. These findings suggest that dibenzalacetone, efficiently synthesized via sonochemistry, not only achieves a high yield but also has potential as an antibacterial agent against E. coli. This research highlights the efficacy of sonochemistry for the rapid and effective synthesis of compounds with significant medical applications.